La lectura como recurso innovador para mejorar la creación literaria en los estudiantes de primer curso de bachillerato del colegio Pío Jaramillo Alvarado de la ciudad de Loja. Periodo académico 2014-2015 - Paccha Alverca, Sandra Luisa (2016)
Theinvestigativeworktitled: READING AS AN INNOVATIVE RESOURCE TO IMPROVE THE LITERARY CREATION IN STUDENTS OF FIRST COURSE OF BACHELOR OF THE COLLEGE PIO JARAMILLO ALVARADO OF THE CITY OF SHOP. ACADEMIC PERIOD 2014-2015, itwasproposed as a general objective, toanalyzereading as aninnovativeresourcetoimprovetheliterarycreation of thestudents of thefirstyear of the Pío Jaramillo Alvarado High School. Themethodsusedwere: thescientific, thedescriptive, theanalytic-synthetic and inductive-deductive, eachapplied in theirfield of study. Thetechniquesusedwerecomposed of thesurvey, thestructured interview and thebibliographictechnique; Whiletheinstrumentsusedwerethequestionnaire and thestructured interview guide. Amongthemainconclusionsreached, it can be seenthatfirst-yearhighschoolstudentshavehadlittlemotivationtoread, sinceLanguage and Literatureteachers do not use itfrequently, thisisduetothe short time withtheWhichcountfortheseactivities in theirclassperiods, results in thelittlepractice of reading as aninnovativeresourceforliterarycreation. In addition, thestudentsaffirmthat in thoseoccasionswheretheteacher has made use of reading as such, theyhavebeenabletoobtaineffectivelearning, whichallowsustoassimilatethattherelationshipbetweenreading as aninnovativeresource and literarycreationisgood, Itisrecommendedthatteachersmakeconstant use of readingtoimparttheirclasseswitheasetoimprovetheiracademic performance